In Utero Efavirenz Exposure and Neurodevelopmental Outcomes in HIV-exposed Uninfected Children in Botswana. Issue 8 (August 2019) - Cassidy, Adam R.; Williams, Paige L.; Leidner, Jean; Mayondi, Gloria; Ajibola, Gbolahan; Makhema, Joseph; Holding, Penny A.; Powis, Kathleen M.; Batlang, Oganne; Petlo, Chipo; Shapiro, Roger; Kammerer, Betsy; et al.
Abstract : Background: Minimal data exist related to neurodevelopment after in utero exposure to Efavirenz (EFV). We sought to compare neurodevelopmental outcomes in HIV-exposed/uninfected (HEU) children with in utero exposure to EFV-based triple antiretroviral treatment (ART) versus non-EFV-based ART, and to examine whether timing of initial EFV exposure is associated with neurodevelopment deficits. Methods: Women living with HIV who had received EFV-based ART during pregnancy and whose HEU newborn participated in a prior study were reconsented for their HEU toddler to undergo neurodevelopmental testing at 24 months old. We administered the Bayley Scales of Infant and Toddler Development, Third Edition (BSID-III), Developmental Milestones Checklist (DMC) and Profile of Social Emotional Development (PSED). We compared outcomes to previously-collected data from a cohort of 24-month-old HEU children with in utero exposure to non-EFV-based ART. Adjusted general linear models were used to compare mean outcomes. Results: Our analysis included 493 HEU children (126 EFV-exposed, 367 EFV-unexposed). Adjusted mean scores for the EFV-exposed group were worse than the EFV-unexposed group on BSID-III Receptive Language (adjusted means = 21.5 vs. 22.5, P = 0.05), DMC Locomotor (30.7 vs. 32.0, P < 0.01) and Fine Motor scales (17.8 vs. 19.2, P < 0.01); and PSED (11.7 vs. 9.9, P = 0.02); but better on the DMC Language scale (17.6 vs. 16.5, P = 0.01). Earlier (vs. later) EFV exposure was associated with worse scores on the BSID-III Receptive Language scale (20.7 vs. 22.2, P = 0.02). Conclusions: HEU children exposed in utero to EFV-based ART may be at higher risk for neurodevelopmental and social-emotional deficits than HEU children exposed to non-EFV-based ART.